Reproductive Performance of Crossbreed Cows on Lowland Terrain - Ardiyansyah, Septiana Alafia Yusi; Sri Agus Sudjarwo; Nusdianto Triakoso; Tri Wahyu Suprayogi; Ismudiono Ismudiono; Oky Setyo Widodo (Ovozoa: Journal of Animal Reproduction, 2023)
This study aims to identify the differences in reproduction performance of Ongole cross (PO), Limousine cross (Limpo), and Simmental cross (Simpo) in Kerek district, Tuban regency. Primary data was taken by interviewing inseminators and farmers, while secondary data was taken from the Fisheries and Animal Husbandry Department of Tuban regency. The total sample was 360 cows consisting of 30 PO, Limpo, and Simpo cows aged 3, 4, 5, and 6 years respectively which were calculated based on the Roscoe formula. Data was analyzed using the Simple Linear Regression and ANOVA followed by Duncan's multiple range test at a significance level of 95%. The results showed that the services per conception (S/C), conception rate (CR), and calving rate (CvR) were not significantly different (p >0.05) between PO, Limpo and Simpo cows. Meanwhile, days open (DO) and fertility status (FS) of PO cows were higher (p <0.05) than Limpo and Simpo cows. There was no significant difference (p >0.05) in DO and FS between Limpo and Simpo cows. The linear equation with age as a predictor (X) of S/C, DO, and CI (Y) values were not significant (p >0.05) in PO, Limpo, and Simpo cows. It could be concluded that the reproductive performance of PO cows was better than Limpo and Simpo cows.